2013
DOI: 10.3382/ps.2013-03029
|View full text |Cite
|
Sign up to set email alerts
|

β-1,3/1,6-Glucan alleviated intestinal mucosal barrier impairment of broiler chickens challenged with Salmonella enterica serovar Typhimurium

Abstract: This study investigated the protective effect of β-1,3/1,6-glucan on gut morphology, intestinal epithelial tight junctions, and bacterial translocation of broiler chickens challenged with Salmonella enterica serovar Typhimurium. Ninety Salmonella-free Arbor Acre male broiler chickens were randomly divided into 3 groups: negative control group (NC), Salmonella Typhimurium-infected positive group (PC), and the Salmonella Typhimurium-infected group with dietary 100 mg/kg of β-1,3/1,6-glucan supplementation (T) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
115
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 57 publications
15
115
0
4
Order By: Relevance
“…Therefore, intestinal TJ proteins could improve gut integrity and nutrient absorption, thereby increasing the growth rate in Thai-breed chickens. TJs are also related to innate mucosal immunity, protecting the host from bacterial colonization and invasion to the submucosa (8,17). It was found that these molecules were present in significantly low numbers in Thai-breed chickens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, intestinal TJ proteins could improve gut integrity and nutrient absorption, thereby increasing the growth rate in Thai-breed chickens. TJs are also related to innate mucosal immunity, protecting the host from bacterial colonization and invasion to the submucosa (8,17). It was found that these molecules were present in significantly low numbers in Thai-breed chickens.…”
Section: Discussionmentioning
confidence: 99%
“…It is also found in the intestinal crypts of chickens (15). Antimicrobial defensin peptides from Paneth cells form a gradient within the mucosal layer on the epithelial surface (14) and aid antimicrobials against both gramnegative and positive bacteria (8,(15)(16)(17)(18). The temporary weakening of the mucosal surface and lower amount of β-defensin resulted in the intestine being more penetrable to intraluminal bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations